Etniczne uwarunkowania sukcesu edukacyjnego. Młodzież eskimoska w szkolnictwie Alaski i Arktycznej Kanady - Gmerek, Tomasz (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article deals with the issue of the relation between education, ethnicity and educational success of Inuit (Eskimo) Youth in Alaska and Arctic Canada. Particular emphasis was placed on reconstructing educational practices and the educational policy that is implemented toward indigenous minorities within school system (especially assimilation, discrimination, marginalization and revitalization of ethnic identity). An attempt was made at examining the relationship between schooling, socialization, language policy, and the development of aboriginal youth in Alaska and Canada.
Keywords: assimilation